Impact of targeted intervention using a collaborative approach for oral third-generation cephalosporins: An interrupted time-series analysis - Ryo Yamaguchi; Koh Okamoto; Takehito Yamamoto; Sohei Harada; Takehiro Tanaka; Hiroshi Suzuki; Kyoji Moriya (Cambridge University Press, 2022)
Abstract Objectives: To assess the effectiveness of a targeted intervention using a collaborative approach, added to a comprehensive educational intervention, to facilitate the appropriate use of oral third-generation cephalosporins (3GCs). Design: Quasi-experimental study. Setting: The University of Tokyo Hospital, a tertiary-care teaching hospital. Participants: Approximately 2,000,000 outpatients and 80,000 inpatients at the hospital between April 2017 and March 2020. Intervention: The targeted intervention using the collaborative approach was implemented in the departments with the highest use of oral 3GCs (ophthalmology and dermatology departments). Interrupted time-series analysis was applied to assess the change in days of therapy (DOT) of oral 3GCs between the preintervention period (April 2017-April 2019) and the postintervention period (May 2019-March 2020) for both inpatients and outpatients. Results: After the introduction of the targeted intervention with oral 3GCs, a significant immediate reduction of 13.48 DOT per 1,000 patient days was detected in inpatients (P < .001). However, no significant change in slope was observed before and after the intervention (−0.02 DOT per 1,000 patient days per month; P = .94). Although a temporary increase was observed after the targeted intervention in outpatients, the slope significantly decreased (−0.69 DOT per 1,000 outpatient visits per month; P = .044). No differences were observed in the use of other oral antibiotics after the intervention. Conclusions: The targeted intervention contributed to a reduction in DOT of oral 3GCs in both inpatients and outpatients. Targeted interventions using a collaborative approach might be helpful in further decreasing the inappropriate use of antibiotics.